Pelatihan Aspek Ilmu Kebumian bagi Mahasiswa Manajemen Bisnis Pariwisata Poltesa sebagai Pemandu Wisata dalam Mengembangkan Geowisata Temajuk Sambas: Training on Aspects of Earth Science for Poltesa Tourism Business Management Students as Tour Guides in Developing Geotourism of Temajuk Sambas - Nirmala, Azwa; Mukhtar, Wahdaniah; Murad, Murad; Setiawati, Septami (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
A conservation-based tourism paradigm is needed to face the new normality of the tourism sector in Temajuk village, Sambas Regency, after the COVID-19 pandemic. This conservation is carried out by harmonizing the needs of local communities and tourists. Knowledge related to conservation, including biotic, abiotic, and cultural factors, must be disseminated to tour guides, especially local ones. This Community Service (PKM) activity aims to assist local tour guides regarding conservation steps for geotourism objects. Assistance activities include socialization, tour guide training (in class and the field), collaborative networks between local tour guides, marketing strategies, and promoting the Temajuk Sambas tourist destination area. Training and assistance are provided to students of the Poltesa Tourism Business Management study program (Sambas State Polytechnic) as local guides from one of the geo-tourism destinations in the Temajuk Sambas area, such as J Lo Beach. As a result of this activity, tour guides now understand that conservation is part of geotourism objectives that must be implemented to ensure the sustainability of meeting the needs of local communities, tourists, and the environment.